Optimalisasi Youtube sebagai Sarana Menyalurkan Kreativitas Mahasiswa Pendidikan Anak Usia Dini - Ana Falera (Universitas Islam Tribakti Lirboyo Kediri, 2022)
Early Childhood Education (PAUD) students are prospective Early Childhood Educators (AUD) where students are required to be creative in carrying out learning. Creative in terms of conditioning the classroom atmosphere, creative in making learning media, creative in choosing tools and materials, and also creative in all fields in order to create fun learning for children and not get bored easily. Optimizing youtube as a means to channel the creativity of PAUD students starting from creating a youtube channel, making video upload guidelines, making a video upload schedule, conducting socialization, evaluating, and finally disseminating the uploaded video link. This study uses a qualitative method by describing the results of research on research subjects, namely PAUD students. Collecting data in this study using interview, observation, and documentation techniques using interview and observation instruments. Triangulation techniques are also carried out so that the validity of the data is maintained. Furthermore, data analysis was carried out starting from data reduction, data presentation, and finally drawing conclusions. The results showed that with the encouragement of students to make videos on a regular basis, it trained students to have creative abilities. By getting students to be creative since they were in college, it creates graduates who already have strong creative abilities and are ready to become PAUD educators.